IMPLICATIONS OF USING THE CASE METHOD TO IMPROVE CRITICAL THINKING SKILLS IN INDONESIA - Yani,; Maryani, Enok; Yani, Ahmad (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Forming human resources is the key to a country's progress. Quality human resources have good critical power. People who can think critically can use the information or ideas they have to solve problems. The formation of critical thinking skills can be developed through education. The case method is the answer to developing students' critical powers. The aim of this research is to see the effect of the case method on students' critical thinking abilities. The method used is a literature review by examining related articles. The results of the analysis of several articles show that the case method is a learning method that can improve critical thinking skills. It is hoped that applying the case method will become a method that can be applied in more active and meaningful learning.